Rif1: A Conserved Regulator of DNA Replication and Repair Hijacked by Telomeres in Yeasts - Mattarocci, Stefano; Hafner, Lukas; Lezaja, Aleksandra; Shyian, Maksym; Shore, David (Frontiers in Genetics, 2016)
Rif1 was originally identified in the budding yeast S. cerevisiae as a telomere-binding protein that negatively regulates telomerase-mediated telomere elongation. Although this function is conserved in the distantly related fission yeast S. pombe, recent studies, both in yeasts and in metazoans, reveal that Rif1 also functions more globally, both in the temporal control of DNA replication and in DNA repair. Rif1 proteins are large and characterized by N-terminal HEAT repeats, predicted to form an elongated alpha-helical structure. In addition, all Rif1 homologues contain two short motifs, abbreviated RVxF/SILK, that are implicated in recruitment of the PP1 (yeast Glc7) phosphatase. In yeasts the RVxF/SILK domains have been shown to play a role in control of DNA replication initiation, at least in part through targeted de-phosphorylation of proteins in the pre-Replication Complex. In human cells Rif1 is recruited to DNA double-strand breaks through an interaction with 53BP1 where it counteracts DNA resection, thus promoting repair by non-homologous end-joining. This function requires the N-terminal HEAT repeat-containing domain. Interestingly, this domain is also implicated in DNA end protection at un-capped telomeres in yeast. We conclude by discussing the deployment of Rif1 at telomeres in yeasts from both an evolutionary perspective and in light of its recently discovered global functions.